Knowledge, attitudes, concern, behaviors, and barriers associated with the readiness to receive seasonal influenza vaccine among healthcare workers in oncology setting during the COVID-19 pandemic - Sawsan Mubarak; Hadeel AlGhawrie; Bayan Qaddumi (Human Vaccines & Immunotherapeutics, 2023)
This study examines the knowledge, attitudes, concerns, behaviors, and barriers related to seasonal influenza vaccination among healthcare workers (HCWs) in the oncology setting during the COVID-19 pandemic. The objective is to assess the readiness of HCWs to receive the influenza vaccine. A cross-sectional study was conducted at the King Hussein Cancer Center (KHCC) in Amman, Jordan. HCWs were surveyed using a self-administered web-based questionnaire between October 2021 and November 2021. Among 223 participants, the coverage rates for seasonal influenza vaccination ranged from 65% to 81% during the autumns of 2019 and 2020, respectively. These vaccination rates showed a significant increase despite the challenges posed by the COVID-19 pandemic. Furthermore, 89.1% of the participants expressed their intention to receive the vaccine in the autumn of 2021. The analysis revealed a significant association between receiving the influenza vaccine in 2020 and the participants’ work experience (P < .001, respectively). Additionally, receiving the influenza vaccination was significantly associated with higher knowledge levels (P = .036, 0.015). Although knowledge about the influenza vaccine was generally high, concerns and barriers were identified. This study demonstrates a high rate of influenza vaccination among HCWs during the COVID-19 pandemic. The participants also expressed a strong willingness to receive the vaccine in the post-pandemic season and exhibited good knowledge about it. However, concerns and barriers related to vaccination remain. These findings emphasize the importance of addressing these concerns and barriers to further enhance influenza vaccination rates among HCWs.